Building Green Schools Through Adiwiyata School in Indonesia - Lestari, Ambar Sri; La Fua, Jumardin; Wahyuni, Imelda (Proceeding International Conference on Religion, Science and Education, 2022)
This study aims to explore Green Schools through Adiwiyata School program in Environmental education that contributes to sustainable environmental problems. This study uses an interpretive approach to data collection and analysis (Thanh and Thanh 2015), which aims to understand individuals related to experiences in building environments through Adiwiyata Program. Participants in this study are schools that have realized the Adiwiyata program, both public schools and private schools. The research findings show that building a Green School starts from activities of schools to foster self-awareness in overcoming environmental problems which are integrated into the Environmental Education curriculum. This research has implications for the participation and collaboration between schools and the community in realizing an environmentally friendly Adiwiyata School.